Ayurvedic Management of Asrgdhara - Namitha S.N (International Journal of Ayurveda and Pharma Research, 2025)
Asrgdhara is a condition of ‘Raja pradeerana’, that is excessive flow of Raja or Arthava. One who follows the Nidana sevana like Lavana, Amla, Guru aharas, Snigdha aharas, Adhyashana, h/o Garbha pata etc. can result in Asrgdhara. This can be corelated to abnormal uterine bleeding. Present case study is about a patient with heavy menstrual bleeding with dysmenorrhea and passage of clots after attaining menstruation following her delivery and irregular cycles since menarche. In modern she was suggested for hysterectomy since her family is completed but patient denied. Here, after taking a detailed menstrual and personal history, the Doshas involved were analysed as Vata and Kapha. Since Asrgdhara is a Basti Sadhya vyadhi and following the Samanya chikitsa, the treatment plan was done. Treatment plan included Picha basti and required internal medications. Patient had significant symptomatic relief with gradual reduction in clots to no clots, reduced dysmenorrhea and also the cycles became regular within 3 months of intervention. This case is a perfect example for conditions where even after suggesting surgical management, how Ayurveda helps in leading a healthy life by bringing the condition under complete control.